A unique two-phase heterostructure with cubic NiSe2 and orthorhombic NiSe2 for enhanced lithium ion storage and electrocatalysis. Issue 34 (12th August 2022) - Wang, Dong; Li, Li; Liu, Zhichao; Gao, Shanshan; Zhang, Guangshuai; Hou, Yongzhao; Wen, Guangwu; Zhang, Lijuan; Gu, Hao; Zhang, Rui
Abstract : A unique heterostructure constructed with cubic NiSe2 and orthorhombic NiSe2 is developed, demonstrating enhanced lithium-ion storage and electrocatalytic HER properties. Abstract : Two-phase heterostructures have received tremendous attention in energy-related fields as high-performance electrode materials. However, heterogeneous interfaces are usually constructed by introducing foreign elements, which disturbs the investigation of the intrinsic effect of the two-phase heterostructure. Herein, unique heterostructures constructed with orthorhombic NiSe2 and cubic NiSe2 phases are developed, which are embedded in in situ formed porous carbon from metal–organic frameworks (MOFs) (O/C-NiSe2 @C). Precisely-controlled selenylation of MOFs is crucial for the formation of the O/C-NiSe2 heterostructure. The heterogeneous interfaces with lattice dislocations and charge distribution are conducive to the high-speed transfer of electrons and ions during electrochemical processes, so as to improve the electrochemical reaction kinetics for lithium-ion storage and the hydrogen evolution reaction (HER). When used as the anode of lithium-ion batteries (LIBs), O/C-NiSe2 @C shows a superior electrochemical performance to the counterparts with only the cubic phase (C-NiSe2 @C), in view of the cycling performance (719.3 mA h g −1 at 0.1 A g −1 for 100 cycles; 456.3 mA h g −1 at 1 A g −1 for 1000 cycles) and rate capabilities (344.8 mA h g −1 at 4 A g −1 ). Furthermore, O/C-NiSe2 @C also exhibits better HER properties than C-NiSe2 @C, that is, much lower overpotentials of 154 mV and 205 mV in 0.5 M H2 SO4 and 1 M KOH, respectively, at 10 mA cm −2, a smaller Tafel slope as well as stable electrocatalytic activities for 2000 cycles/10 h. Preliminary observations indicate that the unique orthorhombic/cubic two-phase heterostructure could significantly improve the electrochemical performance of NiSe2 without additional modifications such as doping, suggesting the O/C-NiSe2 heterostructure as a promising bifunctional electrode for energy conversion and storage applications.